Studying Early Maladaptive Schemas and Personality Factors in Betraying and Injured Spouses - Vajiheh Shariati; Elham Taheri; Ghazaleh Garivani (Shahid Beheshti University of Medical Sciences, 2022)
Backgrond :The family foundation is established by marriage. What is of utmost importance, is marital satisfaction which is one of the crucial concepts for the evaluation of happiness and stability in marriage. Methods:The present research study is an applied descriptive-correlational and causal-comparative research ,aimed at studying the early maladaptive schemes and personality factors in the betraying spouses and those injured by betrayal.The statistical population of the present study included all betraying and injured couples and also ordinary married people of Mashhad city in 2020. They participated online in the study due to the coronavirus outbreak. To collect data, the Young Early Maladaptive Schemas Questionnaire (Short Form) and Millon Clinical Multiaxial Inventory (MCMI) were used and collected using Pearson correlation coefficient, discriminant diagnostic analysis, and multivariate analysis of variance (MANOVA) were analyzed in SPSS 22 software. Result: There was a positive meaningful relationship between early maladaptive schemas with all personality factors among betraying partners and  meaningful relationship between the maladaptive schemas with all personality factors except the self-destructive, schizotypal, and borderline disorder.Early maladaptive schemas and personality factors were able to predict marital infidelity in the injured group and betraying one; there was a meaningful difference between the three betraying, injured, and normal groups in terms of early maladaptive schemas and personality factors. two betraying and injured groups had higher maladaptive schemas and personality factors compared to the normal group. Conclusion:Marital infidelity can have severe emotional consequences for the injured couple.